Photosynthetic carbon metabolism in leaves of transgenic tobacco (Nicotiana tabacum L.) containing decreased amounts of fructose 2,6-bisphosphate. - Scott, P; Lange, A; Kruger, N (2000)
The aim of this work was to examine the role of fructose 2,6-bisphosphate (Fru-2,6-P2) in photosynthetic carbon partitioning. The amount of Fru-2,6-P2 in leaves of tobacco (Nicotiana tabacum L. cv. Samsun) was reduced by introduction of a modified mammalian gene encoding a functional fructose-2,6-bisphosphatase (EC 3.1.3.46). Expression of this gene in transgenic plants reduced the Fru-2,6-P2 content of darkened leaves to between 54% and 80% of that in untransformed plants. During the first 30 min of photosynthesis sucrose accumulated more rapidly in the transgenic lines than in the untransformed plants, whereas starch production was slower in the transgenic plants. On illumination, the proportion of 14CO2 converted to sucrose was greater in leaf disks of transgenic lines possessing reduced amounts of Fru-2,6-P2 than in those of the control plants, and there was a corresponding decrease in the proportion of carbon assimilated to starch in the transgenic lines. Furthermore, plants with smaller amounts of Fru-2,6-P2 had lower rates of net CO2 assimilation. In illuminated leaves, decreasing the amount of Fru-2,6-P2 resulted in greater amounts of hexose phosphates, but smaller amounts of 3-phosphoglycerate and dihydroxyacetone phosphate. These differences are interpreted in terms of decreased inhibition of cytosolic fructose-1,6-bisphosphatase resulting from the lowered Fru-2,6-P2 content. The data provide direct evidence for the importance of Fru-2,6-P2 in co-ordinating chloroplastic and cytosolic carbohydrate metabolism in leaves in the light.